Applied econometric time series - Enders, Walter, 1948- (Hoboken, NJ : John Wiley and Sons, Inc., 2015)
Applied Econometric Time Series, 4th Edition demonstrates modern techniques for developing models capable of forecasting, interpreting, and testing hypotheses concerning economic data. In this text, Dr. Walter Enders commits to using a "learn-by-doing" approach to help readers master time-series analysis efficiently and effectively.
Difference equations -- Stationary time-series models -- Modeling volatility -- Models with trend -- Multiequation time-series models -- Cointegration and error-correction models -- Nonlinear models and breaks.
Includes index.
Description based on online resource; title from digital title page (viewed on March 25, 2021).
Master record variable field(s) change: 050
Keywords: Econometrics; Time-series analysis; BUSINESS & ECONOMICS -- Econometrics; Econometrics; Time-series analysis; Ökonometrie; Statistik; Zeitreihe; Zeitreihenanalyse; elektronické knihy; electronic books